Relationship between Gross Motor Coordination and Health-Related Fitness in Serbian Preschool Children - Nenad Stojiljković; Nebojša Trajković; Doroteja Rančić; Mihai Olanescu; Adrian Suciu; Danut Popa (MDPI AG, 2024)
Background: The relationship between motor coordination and physical fitness in preschool children is of significant interest due to its implications for overall health and development. This study aims to investigate the correlation between gross motor coordination, as assessed by the Körperkoordinationstest für Kinder (KTK), and health-related physical fitness components. Methods: A cross-sectional study, involving 139 preschool-aged children, was conducted. Physical fitness was assessed using the PREFIT fitness test battery, which includes measures of flexibility, muscular strength, speed/agility, and cardiorespiratory fitness. Motor coordination was evaluated using the KTK test, comprising four subtests. Results: Pearson correlation analysis revealed weak to strong positive and negative correlations between motor coordination and various physical fitness measures, including flexibility (r = 0.402; p = 0.01), muscular strength (r = 0.178; r = 0.487; r = 0.601; p < 0.05), speed/agility (r = −0.742; p = 0.01), and endurance (r = 0.539; p = 0.01). Additionally, hierarchical regression analysis demonstrated significant influence of motor coordination on physical fitness, explaining a notable percentage of the variance across different fitness components (3.2-55%). Conclusions: The findings underscore the importance of motor coordination in shaping physical fitness levels in preschool children. Promoting motor coordination skills early in childhood may have long-term benefits for overall health and fitness.